Protagoras and Meno - Plato (London, 2005)
Exploring the question of what exactly makes good people good, Protagoras and Meno are two of the most enjoyable and accessible of all of Plato's dialogues. Widely regarded as his finest dramatic work, the Protagoras, set during the golden age of Pericles, pits a youthful Socrates against the revered sophist Protagoras, whose brilliance and humanity make him one f the most interesting and likeable of Socrates' philosophical opponents, and turns their encounter into a genuine and lively battle of minds.
Keywords: Platonic philosophy